Maintaining cultural values across generations in Vietnamese migrant families in Melbourne-Australia - Trần, Thị Thanh Giang (2021)
The Vietnamese family is seen to play highly important role in transmitting, reinforcing and preserving traditional Vietnamese values. It is also thought that family is a central place for educating children about rituals and traditional values that are selected and developed over generations. by sharing between generations, cultural values persist in families.